Curcumin: recent updates on gastrointestinal cancers - Muhammad Imran; Farhan Saeed; Suliman A. Alsagaby; Ali Imran; Ishtiaque Ahmad; Ahmad H. El Ghorab; Mohamed A. Abdelgawad; Tahira Batool Qaisrani; Tahir Mehmood; Maryam Umar; Muhammad Arslan Mumtaz; Arfaa Sajid; et al. (CyTA - Journal of Food, 2023)
ABSTRACTCurcumin is a phenolic pigment, naturally present in Curcuma longa species. It is a yellow active ingredient and shows a pivotal role in the modulation of biological processes resulting in the prevention of cancer particularly due to its radical scavenging activities. In gastrointestinal cancer cells, curcumin has been shown to induce cell death through apoptosis and to cause cell cycle arrest, down-regulating glycolytic enzyme expressions alongside inhibition of the matrix metalloproteinase-2 (MMP-2) promoter activity and SDF-1α-induced cell invasion. It also activates the expression of cleaved caspase-3, reduces cell viability, regulates the ratio of Bcl-2/Bax, decreases the number of cells in the proliferative G0/G1 phase and increases the number of cells in the S phase. Additionally, curcumin prevents DNA from replication during the S phase. This review discusses the chemo-preventive role of curcumin and its mechanisms against human gastrointestinal cancers to understand its activity and potential utilization as a therapeutic moiety.